2016
DOI: 10.1152/ajpregu.00315.2014
|View full text |Cite
|
Sign up to set email alerts
|

ZnT4 (SLC30A4)-null (“lethal milk”) mice have defects in mammary gland secretion and hallmarks of precocious involution during lactation

Abstract: McCormick NH, Lee S, Hennigar SR, Kelleher SL. ZnT4 (SLC30A4)-null ("lethal milk") mice have defects in mammary gland secretion and hallmarks of precocious involution during lactation. Am J Physiol Regul Integr Comp Physiol 310: R33-R40, 2016. First published November 4, 2015 doi:10.1152/ajpregu.00315.2014.-During lactation, highly specialized secretory mammary epithelial cells (MECs) produce and secrete huge quantities of nutrients and nonnutritive factors into breast milk. The zinc (Zn) transporter ZnT4 (SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…With time, low zinc-concentrations were lethal for suckling pups. ZnT4 has profound consequences on mammary epithelial cell function and negatively influences nutrition secretion into the milk, and additionally promotes tissue remodeling in the mammary gland during early lactation [ 315 ]. Animal studies in mice bearing a malfunction of ZnT4, showed these defects to be associated with decreased Akt expression, and Signal transducer and activator of transcription 5 (STAT5) activation.…”
Section: Zinc Deficiency In the Context Of Diseasementioning
confidence: 99%
“…With time, low zinc-concentrations were lethal for suckling pups. ZnT4 has profound consequences on mammary epithelial cell function and negatively influences nutrition secretion into the milk, and additionally promotes tissue remodeling in the mammary gland during early lactation [ 315 ]. Animal studies in mice bearing a malfunction of ZnT4, showed these defects to be associated with decreased Akt expression, and Signal transducer and activator of transcription 5 (STAT5) activation.…”
Section: Zinc Deficiency In the Context Of Diseasementioning
confidence: 99%
“…A spontaneous Znt4 mutant mouse produces milk with reduced zinc levels, so-called lethal milk because pups nursed by these dams die before weaning [ 132 ]. Recently, the Znt4 mutant mouse was shown to have defects in mammary gland secretion and hallmarks of precocious involution during lactation [ 133 ] . Znt5 KO mice display poor growth, osteopenia, and male-specific sudden cardiac death [ 134 ], and also show cytokine production defects in mast cells, which is mediated by the high-affinity immunoglobulin E receptor [ 135 ].…”
Section: Cellular Zinc Homeostasis Involving Zip and Znt Zinc Tranmentioning
confidence: 99%
“…These vesicles differ from intracellular vesicular/organellar stores of zinc, as ZIP transporters do not seem to counteract the action of the ZnT transporters (ZnT2, 3, and 8) loading these vesicles with zinc ions. The “lethal milk” mouse has a truncated form of ZnT4, and presents with low zinc concentration in the milk and developmental defects of the mammary gland [ 17 ]. Zinc transporters ZnT4–7 are involved in loading zinc-requiring ectoenzymes with zinc at the trans Golgi network (TGN)/early secretory pathway [ 18 ].…”
Section: Control Of Cellular Zinc Homeostasismentioning
confidence: 99%